2002
DOI: 10.1046/j.1537-2995.2002.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the effect of transfusing only phenotype‐matched RBCs to patients with sickle cell disease: theoretical and practical implications

Abstract: Limited phenotype matching would have prevented all alloantibodies in 53.3 percent of the patients who formed alloantibodies. This protocol requires RBCs that are readily available. Extended phenotype matching would have prevented alloimmunization in 70.8 percent of patients who formed alloantibodies. However, this would require phenotypes that are 22.7 times less prevalent among random blood donors and is therefore impractical for a long-term strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
178
0
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(194 citation statements)
references
References 27 publications
6
178
0
10
Order By: Relevance
“…However, the immunological processes that occur during various SCD complications make it difficult to ascertain why ACS and VOC may be associated with significantly higher alloimmunization rates than other acute SCD-related complications. Consistent with previous reports (Rosse et al, 1990;Tahhan et al, 1994;Vichinsky et al, 2001;Aygun et al, 2002;Castro et al, 2002;Sakhalkar et al, 2005;Lasalle-Williams et al, 2011), we also observed that unmatched (CEK) transfusion was associated with an increased risk of alloimmunization in both univariate and multivariate analysis. In fact we observed the same alloimmunization rate (2Á6%) in CEK matched transfusions as reported by Sakhalkar et al (2005), and detected no antibodies following level 3 or higher matching despite the fact that our transfusions were strictly administered to a SCD population defined as 'responders.'…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the immunological processes that occur during various SCD complications make it difficult to ascertain why ACS and VOC may be associated with significantly higher alloimmunization rates than other acute SCD-related complications. Consistent with previous reports (Rosse et al, 1990;Tahhan et al, 1994;Vichinsky et al, 2001;Aygun et al, 2002;Castro et al, 2002;Sakhalkar et al, 2005;Lasalle-Williams et al, 2011), we also observed that unmatched (CEK) transfusion was associated with an increased risk of alloimmunization in both univariate and multivariate analysis. In fact we observed the same alloimmunization rate (2Á6%) in CEK matched transfusions as reported by Sakhalkar et al (2005), and detected no antibodies following level 3 or higher matching despite the fact that our transfusions were strictly administered to a SCD population defined as 'responders.'…”
Section: Discussionsupporting
confidence: 92%
“…RBC transfusions also prove to be life saving for acute sickle-related complications, such as acute ischaemic stroke, acute chest syndrome (ACS), splenic sequestration and aplastic crisis. However, transfusion of RBCs is complicated by development of allo-and auto-antibodies, which occur much more frequently in patients with SCD than in any other heavily transfused patient population (alloimmunization rates 18-47% for SCD vs. 7-19% for thalassaemia major (Rosse et al, 1990;Heddle et al, 1995;Hoeltge et al, 1995;Aygun et al, 2002;Castro et al, 2002;Azarkeivan et al, 2011;Thompson et al, 2011;Vichinsky et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…From a medical perspective, minority underrepresentation can cause problems in the supply of matching blood and tissue products (Castro et al, 2002;Shaz et al, 2008). Various minority groups differ from a country's majority population because of genetic differences in blood group and tissue antigen expression.…”
Section: Introduction Why Recruiting Minority Blood Donors Is So Impomentioning
confidence: 99%
“…The exact number of cumulative transfusions from birth to first antibody formation is often not reported and in many studies it is unclear if the transfusion history has been fully traced, including transfusions outside the reporting centers [9,10,12,[14][15][16]28]. Yet, the exposure to foreign RBC antigens is a prerequisite for alloimmunization and higher incidences of alloimmunization have been observed in patients with a higher number of transfusions [5,7,8,27,29].…”
mentioning
confidence: 99%